Assessing an alpha-defensin lateral flow device for diagnosing septic arthritis: reporting on a false-negative case and a false-positive case. (2nd January 2020) - Narita, Atsushi; Suzuki, Akemi; Nakajima, Taku; Takakubo, Yuya; Ito, Juji; Sasaki, Akiko; Takagi, Michiaki
Abstract: Alpha-defensin (αD), an antimicrobial peptide released by neutrophils in response to bacterial pathogens, was proposed as a novel diagnostic biomarker in synovial fluid. Several reports have shown that αD can serve as a reliable biomarker in the diagnosis of periprosthetic joint infection (PJI). We assessed whether αD could also serve to diagnosis of septic arthritis, a similarly difficult to diagnose PJI. To our knowledge, besides PJI, few reports exist assessing the utility of αD for septic arthritis. We have attempted to diagnose several cases of suspected septic arthritis using the Synovasure ® αD detection lateral flow device. We report a false-positive case and a false-negative case. The false-negative case we experienced was caused by Staphylococcus capitis, which is coagulase-negative, and possibly represents a low virulence micro-organism infection. The false-positive case was ultimately diagnosed as seronegative rheumatoid arthritis and possessed calcium pyrophosphate depositions. False positives have been suggested to occur in conditions where neutrophils are mobilised. As for PJI, in cases where diagnosis is difficult, αD can be an additional diagnostic indicator. However, making a definitive diagnosis using the αD lateral flow device alone was found to be difficult. The utility of αD in assessing septic arthritis is inconclusive; therefore, larger prospective clinical studies should be considered for a better assessment.